2016
DOI: 10.1080/13651501.2016.1249489
|View full text |Cite
|
Sign up to set email alerts
|

Past suicidal ideation as an independent risk factor for suicide behaviours in patients with depression

Abstract: The present study suggests that the most severe suicidal ideation throughout one's entire life should not be overlooked and may be a major predictor of the risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 22 publications
0
18
0
3
Order By: Relevance
“…Exclusion criteria included: (1) studies conducted in special populations, such as adolescent or the elderly and (2) data extracted from medical records. Several studies on major depressive episode (MDE) included individuals with dysthymia, such as Seo et al ., 2014 and Park et al ., 2017 or bipolar depressive episode, such as Serafini et al ., 2011 and Wakefield and Schmitz, 2016, therefore these studies were excluded with the exception of those which included only individuals with MDD (following confirmation by the corresponding authors). If more than one paper based on the same dataset were published, only the paper with the largest sample was included.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included: (1) studies conducted in special populations, such as adolescent or the elderly and (2) data extracted from medical records. Several studies on major depressive episode (MDE) included individuals with dysthymia, such as Seo et al ., 2014 and Park et al ., 2017 or bipolar depressive episode, such as Serafini et al ., 2011 and Wakefield and Schmitz, 2016, therefore these studies were excluded with the exception of those which included only individuals with MDD (following confirmation by the corresponding authors). If more than one paper based on the same dataset were published, only the paper with the largest sample was included.…”
Section: Methodsmentioning
confidence: 99%
“…6 Although the fact that CS is a preventable outcome, this phenomenon is limited understood because it is difficult to attain adequate information on deaths by suicide. Considering SI may be a major predictor of the CS among MDD patients 7 and suicide completers with MDD usually had SI, 8 thus much of the research associated with suicidal behavior pays attention to SI among MDD.…”
Section: Introductionmentioning
confidence: 99%
“…SI varies in form and degree of severity, from fleeting thoughts to detailed planning. A meta-analysis of 172 longitudinal studies3 has shown that in adults, SI strongly correlates with suicidal attempt and death by suicide that remains robust even after adjusting for severity of depression and stress-events 4…”
Section: Introductionmentioning
confidence: 99%